2006
DOI: 10.1111/j.1365-2125.2006.02751.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blockers and headache

Abstract: We recently reported a meta-analysis of 94 randomized placebo-controlled trials of blood pressure-lowering drugs in which the prevalence of headache was reported [1]. On average, one-third fewer people reported headache in the treated groups than in the placebo groups [odds ratio (OR) 0.67; 95% confidence interval (CI) 0.61, 0.74; P < 0.001]. There was a statistically significantly reduced prevalence of headache in separate analyses of four classes of blood pressure-lowering drugs, thiazides, β -blockers, ACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Calcium channel blockers seem to be less effective than other drugs in heart failure but the difference in risk reduction is not large (19% v 24%; table 6) and they are no less effective after myocardial infarction. All classes of drug prevent headaches and migraine,48 49 50 although calcium channel blockers do so only in low (half standard) dose 51. There is no evidence to support recommendations for particular classes of drug in older or younger people 47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium channel blockers seem to be less effective than other drugs in heart failure but the difference in risk reduction is not large (19% v 24%; table 6) and they are no less effective after myocardial infarction. All classes of drug prevent headaches and migraine,48 49 50 although calcium channel blockers do so only in low (half standard) dose 51. There is no evidence to support recommendations for particular classes of drug in older or younger people 47.…”
Section: Discussionmentioning
confidence: 99%
“…All classes of drug prevent headaches and migraine, 48 49 50 although calcium channel blockers do so only in low (half standard) dose. 51 There is no evidence to support recommendations for particular classes of drug in older or younger people. 47 A relative contraindication of even cardioselective β blockers in people with airways obstruction or peripheral arterial disease is perceived, 24 but a meta-analysis of trials has shown that cardioselective β blockers do not produce adverse respiratory effects in mild to moderate obstructive airways disease 52 ; such considerations are not a reason to withhold a β blocker, but reinforce the principle that patients should be monitored for side effects of drugs and a drug should be withdrawn if it causes adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Головная боль может быть и нежелательной побочной реакцией (НПР) при применении дигидропиридиновых АК, при этом она является дозозависимой. Поэтому головная боль как НПР может отсутствовать при назначении препаратов этой группы в стартовых дозах, а при увеличении дозы вероятность ее появления значительно возрастает [10]. Головная боль как побочный эффект АК обусловлена их главным механизмом действия -вазодилатацией [9,10].…”
Section: изменение частоты головной боли на фоне антигипертензивной тunclassified
“…The second, and more important, reason is that effects that appear not to be dose‐related are saturated in the therapeutic range but are dose‐related in the range of doses below the therapeutic range; in other words, they are hypersusceptibility reactions [6]. Most adverse reactions, however, are dose‐related within the therapeutic range of doses (collateral reactions), and an elegant example of this is given by Law et al in this issue of the Journal , in which they show that headache due to calcium channel blockers is dose‐related [7]. That they have shown this by a meta‐analysis of published data should encourage others to look for dose relationships elsewhere in the published literature.…”
Section: The Classification Of Adverse Drug Reactions In the 21st Cenmentioning
confidence: 99%